Understanding Minority Shareholders' Perceptions Pertaining To Corporate Governance Practices In Malaysia - Lee, Mun Jye (2010)
Corporate Governance is concerned about the establishment of structures, processes and mechanisms by which businesses and affairs of the firms are directed, managed and monitored. The presence of effective corporate governance mechanisms are believed to generate long term stakeholders‟ values at large through the accountability of managers and enhancing the firms‟ performances. This research makes an attempt to understand the minority shareholders‟ perceptions pertaining to certain corporate governance practices in Malaysia such as the corporate governance and firms‟ performances, the roles and effectiveness of various governance mechanisms, especially the family groups, managers, controlling shareholders and boards of directors of the firms.